The Effect of Product Quality and Service Quality on Customer Loyalty with Customer Satisfaction as an Intervening Variable (Case Study on Muslim Fashion Stores in Wonogiri) - Ghazali, Yovanda Alfian; Sholahuddin, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study was to analyze the effect of product quality and service quality on customer loyalty with customer satisfaction as an intervening variable case study at a Muslim fashion store in Wonogiri. The type of research used by researchers is quantitative research. The data source for this research is primary data. The research population is consumers of 3 Muslim Clothing Stores in Wonogiri City, namely Zoya, Rabbani, and Zalfa. The number of samples in this study was 150 respondents. The sampling method in this research uses Non-probability Sampling with the Purposive Sampling technique. In this study, the analytical technique used was Partial Least Square (PLS) with a calculation process using the SmartPLS 3.0 software program. The results of this study show that Product Quality has a negative and insignificant effect on Customer Satisfaction. Service Quality and Product Quality have a significant positive effect on Customer Satisfaction. Service Quality and Customer Satisfaction have a significant positive effect on Customer Loyalty.